The importance of the development banks for the financial infrastructure - Rainer Jonas (Intereconomics, 1975)
In literature and practice the term “development bank” is commonly applied to investment banks for the financing of private projects which deserve to be promoted on general economic grounds. Their salient task is usually to provide medium- and long-term funds. Complementary consultative functions are occasionally performed as well while other bank transactions, especially of a short-term nature, and debit business were, as a rule, not considered. This concept of the purpose of a development bank has proved too narrow, too normative and too general.
Keywords: 330; Financing